Biotechnological processing of small-sized shrimps for using as seafood - A. P. Yarochkin; G. N. Timchishina; V. N. Akulin; A. N. Bashtovoy; S. P. Kasyanov; I. M. Vigovskaya (Известия ТИНРО)
Main technological and chemical characteristics of small-sized shrimps Pandalus borealis, P. goniurus and krill Euphausia superba are presented. The main processes of this kind of shrimp processing are described, with usage of its own complex of proteinases to produce autoproteolysis products. Lysates of these shrimps have high nutritional value comparable with the value of low-fat cottage cheese, though the shrimp lysate protein is a completely animal protein similar to beef one. As a source of low-fat protein, the shrimp lysates belong to the category of specialized and functional food and food ingredients; they also can de considered as the source of omega-3 fatty acids and astaxanthin. Volatile components of the shrimp lysates contain 30 compounds responsible for taste and aroma properties of crabs and shrimps, as thiran, methylthiran, dimethyldisulfide, thioacetic acid, 2-mercaptopropanoic acid, etc. Safety of shrimps and their lysates is provided by low content of organochlorine compounds, radionuclides, toxic elements and low values of microbiological parameters, below of the maximum permissible levels. The shrimp lysates are suitable for using in manufacture of emulsion and pasty products with high commodity properties, classified as gastronomic products with high taste and nutritional value.